In vitro synthesis of humoral factors (immunoglobulins and complement) in lesional skin of leprosy patients. - Lai A Fat, R F (1979)
An in vitro culture technique was used to demonstrate the synthesis of immunoglobulins and complement in lesional skin of patients representing the entire clinico-histopathological spectrum of leprosy. The results indicate that immunoglobulin G is produced in different amounts in the various forms of leprosy. Classification of the patients according to the three main groups shows that a small amount of immunoglobulin G synthesis occurred in tuberculoid leprosy, a distinct amount occurred in borderline leprosy, and large amount occurred in lepromatous leprosy. Contrary to expectation, synthesis of C3 was found only in some of the cultures of these three forms of leprosy. The function of the locally synthesized immunoglobulin G and the findings concerning C3 synthesis are discussed.